Standalone Attendance Monitoring and Projector System - Ingale, Mohit; Gage, Akshata; Patil, Jitesh; Jog, Gautam; Terdale, Jayprabha (International Journal of Computer Sciences and Engineering, 2025)
SAMP Stands for Standalone Attendance Monitoring and Projector System. It involves four parts, Portable Projector System, Attendance Monitoring System, Remote File Transfer, Online Notice Board. Raspberry Pi is used as central computer, Raspberry Pi has onboard HDMI port which can be used to connect to the projector. Various Linux based Operating System can be installed on PI, RC522 RFID module is interfaced with Pi using SPI communication and data of attendance is logged into SQL database, Raspberry Pi is used as ftp server to transfer file remotely between Raspberry Pi and any computer in network. Raspberry Pi is used as webserver to host html pages, which can be used to host notices.